Board Level Employee Representation and CEO Compensation: The Mediation and Interaction Effects of the Largest Shareholder - Dardour, Ali; Ahmed, Rana (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
The goal of this paper is to study the effect of board employee representation on the CEO compensation in French publicly listed companies. The study shows the following results: First, we found that employee board representation affects negatively and significantly the CEO total compensation. Second, employee representation has no effect on firm financial performance. Third, we found that French State strengthens the control of BLER over CEOs and their compensation, rather than simply mediate it.